Limitations of Accelerated Stability Model Based on the Arrhenius Equation for Shelf Life Estimation of In Vitro Diagnostic Products. (4th December 2020) - Ebrahim, Alireza; DeVore, Karl; Fischer, Tim
Abstract: Background: An accelerated stability model based on the Arrhenius Equation can be used to estimate stability of diagnostic reagents. Here we review 3 examples in which the model does not accurately predict the stability of diagnostic reagents. Methods: We prepared several pilot lots of quality controls materials containing fructosamine, BNP, and HbA1c in human whole blood and serum matrices and performed accelerated stability studies at increased temperatures (5 °C to 35 °C) and real-time stability studies at the recommended storage temperature (-10 °C to -20 °C) for several analytes in quality control materials. Results: We observed that the stability predictions obtained from the accelerated stability studies were longer in 2 instances and much shorter in another than those observed from the real-time stability studies. Conclusions: Due to discrepancies between the stability results from accelerated stability studies and those from the real-time stability studies, we stress the need for caution when reagent manufacturers use the Arrhenius model and recommend that the technical groups and committees assigned to revise CLSI and ISO stability documents highlight the limitations of the accelerated stability model and include more guidance and direction on how and when to use the accelerated stability model.